2019
DOI: 10.1016/j.ssmph.2019.100386
|View full text |Cite
|
Sign up to set email alerts
|

Causal effects of education on sexual and reproductive health in low and middle-income countries: A systematic review and meta-analysis

Abstract: Background Despite strong theoretical grounding, important gaps in knowledge remain regarding the degree to which there is a causal relationship between education and sexual and reproductive health, as many claims have been made based on associations alone. Understanding the extent to which these relationships are causal is important both to inform investments in education and health, as well as to understand the mechanisms underlying these relationships. Methods We con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 45 publications
2
64
0
Order By: Relevance
“…A recently published systematic review of evidence regarding the causal effect of increased access to schooling on age at marriage highlights variation in this relationship between countries and across subgroups within countries. The same review found that, in most quasi-experimental or randomized studies of this relationship, the impact of increased access to schooling on age at marriage was modest (Psaki et al 2019). Where child marriage causes an early end to education, it could have negative consequences for girls' personal development and economic opportunities throughout their lives, which may also affect their children (Sunder 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recently published systematic review of evidence regarding the causal effect of increased access to schooling on age at marriage highlights variation in this relationship between countries and across subgroups within countries. The same review found that, in most quasi-experimental or randomized studies of this relationship, the impact of increased access to schooling on age at marriage was modest (Psaki et al 2019). Where child marriage causes an early end to education, it could have negative consequences for girls' personal development and economic opportunities throughout their lives, which may also affect their children (Sunder 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The same review found that, in most quasi‐experimental or randomized studies of this relationship, the impact of increased access to schooling on age at marriage was modest (Psaki et al. 2019). Where child marriage causes an early end to education, it could have negative consequences for girls’ personal development and economic opportunities throughout their lives, which may also affect their children (Sunder 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, they do not provide information about the reasons for the correlation. Only a few studies employ strategies that aim to identify a causal effect of education on HIV, with varying results (Psaki et al, 2019). Among these, De Neve et al (2015) provides the most convincing evidence of a casual effect, and it is the LINDSKOG AND DUREVALL -643 only study that includes both men and women.…”
mentioning
confidence: 99%
“…Researchers have theorised about the ways in which literacy contributes to better health among women via, for example, the provision of targeted knowledge and the tools to understand health information and engage with health bureaucracies (Rowe et al 2005;LeVine et al 2012;Basu and Stephenson 2005;Glewwe 1999;Jejeebhoy 1995). While few studies have investigated the effects of improvements in literacy on health, a recent systematic review of the literature assessing the evidence for a causal effect of education in low-income countries found that increased grade attainment for women has led to lower fertility, lower HIV prevalence, and lower child mortality in a number of settings (Psaki et al 2019a;Mensch et al 2019b). The findings reported here summarising the results of an impact evaluation of a 19-session intervention demonstrate that access to e-readers with engaging books along with facilitated book groups have the potential to enhance basic literacy and non-verbal reasoning ability in the short term with possible longer-term consequences for the health and wellbeing of young women in a low-income setting.…”
Section: Discussionmentioning
confidence: 99%